In-situ curing electrolyte coating diaphragm as well as preparation method and application thereof

By reuniting solid electrolytes with dispersing agents and flame retardants, and solidifying in situ with dual -component binders to form a diaphragm with electrolyte coating, the interface impedance of existing solid electrolytes is high The problem of low rate and poor mechanical strength has significantly improved the performance and safety of the battery.

CN119381694AInactive Publication Date: 2025-01-28XINXIANG ZHONGKE MEMBRANE MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411961019.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-01-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing pure solid electrolyte separators have problems such as high interface impedance, low ionic conductivity and poor mechanical strength. When adding a large amount of electrolyte to the battery to improve ionic conductivity, the heat resistance and flame retardant performance are not ideal.

Method used

The solid electrolyte is evenly compounded with the dispersant and flame retardant, and after adding a dual component binder, directly coat or immerse it on the polyethylene diaphragm. Essence

Benefits of technology

Improve the filling and adhesion of porous substrates and solid electrolytes, improve the mechanical properties, interface stability and ionic conductivity of the diaphragm, and enhance the cycle life and heat resistance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381694A_ABST
    Figure CN119381694A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium batteries, and particularly relates to an in-situ curing electrolyte coating diaphragm and a preparation method and application thereof.The diaphragm comprises a base membrane and an electrolyte coating cured on the surface of at least one side of the base membrane in situ, and the preparation method comprises the steps that first dispersion liquid is prepared; adding the first dispersion liquid into a two-component binder material, and uniformly stirring to obtain a second dispersion liquid; and directly extruding and coating or dip-coating the second dispersion liquid on a porous polyolefin base membrane, and finally carrying out in-situ thermal polymerization curing to obtain the diaphragm. According to the diaphragm, the electrolyte coating diaphragm with low interface impedance is constructed in one step through in-situ thermocuring, good interface compatibility of an electrode and the electrolyte coating diaphragm is achieved, the mechanical property, interface stability and ionic conductivity of the diaphragm are improved, and before thermal runaway of the battery occurs, the flame retardant absorbs heat and is decomposed to form a stable covering layer, so that the thermal runaway of the battery is prevented. And the breakdown resistance of the diaphragm and the thermal runaway temperature of the battery are improved, and the heat resistance and flame retardance are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to an in-situ solidified electrolyte coating diaphragm and a preparation method and application thereof. Background Art

[0002] Existing commercial liquid electrolytes face many challenges, such as flammability, leakage, and limited operating temperature range, which hinder the development of electrochemical energy storage devices. Quasi-solid electrolytes are expected to overcome these limitations. However, the complete replacement of diaphragms and electrolytes by solid electrolytes requires consideration of performance requirements such as ion conductivity, electronic insulation, physical contact with electrodes, resistance to positive electrode oxidation, resistance to negative electrode reduction, electrochemical stability, thermal stability, air stability, good mechanical stability, and the need for comprehensive low-cost large-scale promotion.

[0003] At present, pure solid electrolyte diaphragms have problems such as high interface impedance, low ion conductivity, and poor mechanical strength. Therefore, solid electrolyte coated diaphragms have been developed to replace ceramic coated diaphragms. Although this diaphragm coating process is compatible with existing processes. However, it has been verified by customers that a large amount of electrolyte must be added when preparing batteries to maintain good interface contact between the electrode material and the electrolyte to improve ion conductivity. Consistent with liquid batteries, the amount of electrolyte added has not been reduced, and its heat resistance and flame retardancy are not ideal. Summary of the invention

[0004] The purpose of the present invention is to provide an in-situ cured electrolyte coating diaphragm and its preparation method and application. First, the solid electrolyte is evenly compounded with a dispersant and a flame retardant, and then a two-component binder is added to the compound and directly coated or dipped on a porous polyolefin diaphragm, and then cured by in-situ thermal polymerization to obtain a diaphragm with an electrolyte coating. After the flame retardant reacts with the two-component binder curing agent, it can be partially filled in the porous polyolefin base film, and the other part is coated on the base film and coated on the surface of the solid electrolyte, and will react with the two-component binder to enter the resin system and become a block of the binder resin. Due to the fluidity of the small molecule flame retardant and the binder monomer of the diaphragm of the present invention, it can enter the pores of the diaphragm, and the base film and the solid electrolyte are tightly connected after thermal curing, which not only improves the compatibility and adhesion of the porous substrate and the solid electrolyte filler, the electrolyte coating and the electrode material, but also improves the mechanical properties of the diaphragm, the interface stability and the ionic conductivity performance, and the cycle life of the battery. On the other hand, a flame retardant is added, which has a boiling point (110-130°C) lower than the melting point of porous polyolefin (PE 137°C, PP 170°C). Before the diaphragm begins to melt and the battery thermal runaway occurs, the flame retardant in the porous polyolefin base film absorbs heat and decomposes to form a stable covering layer to protect the base film from melting and cracking. When the temperature continues to rise, the flame retardant enters the binder resin block to play a role, absorbs heat and decomposes to form a stable covering layer, thereby improving the diaphragm's ability to resist penetration and the battery thermal runaway temperature, and improving heat resistance and flame retardancy. In addition, a small amount of electrolyte can be added to the diaphragm of the present invention to maintain a relatively high ionic conductivity, so that the diaphragm of the present invention has broad application prospects in solid-state batteries, lithium metal batteries, and sodium ion batteries.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is: A method for preparing an in-situ cured electrolyte coating diaphragm comprises the following steps: S1. Prepare a first dispersion: stir a solid electrolyte material, a dispersant, and a flame retardant monomer in a solvent, and then place the mixture in a sand mill to completely disperse the mixture to obtain a first dispersion, wherein the mass ratio of the solid electrolyte material, the dispersant, the flame retardant monomer, and the solvent is (10-40): (0.01-1.2): (0.05-4): (55-90), and the flame retardant monomer is a cyclotriphosphazene flame retardant containing a hydroxyl group or an amino group; S2. Preparing a second dispersion: adding a two-component binder to the first dispersion, wherein the two-component binder is composed of a binder monomer A and a curing agent B, wherein the mass ratio of the binder monomer A, the curing agent B and the solid electrolyte material in the first dispersion is (2-10): (0.06-1): (89-98); S3. Prepare the diaphragm: directly extrusion-coat or dip-coat the second dispersion on the porous polyolefin base membrane, and perform in-situ thermal polymerization and curing at 40-80° C. to obtain an in-situ cured electrolyte coating diaphragm.

[0006] Furthermore, in step S1, the solid electrolyte material is at least one of LATP, LAGP, LLZTO, LLZO, sulfide-oxide electrolyte or LGPS, and the D50 of the solid electrolyte material is from 100nm to 2000nm; the dispersant is at least one of sodium hexametaphosphate, sodium polyphosphate, sodium dodecyl sulfate, polyacrylamide, sodium polyacrylate, polybutyl acrylate-styrene-acrylic acid, polyethylene glycol, polyvinyl pyrrolidone, and maleic anhydride-styrene copolymer; the flame retardant monomer is at least one of hydroxycyclotriphosphazene, aminocyclotriphosphazene, and tripropoxy-triethanolamine cyclotriphosphazene; the sand mill speed is 200-2000 r / min, and the sand milling time is 5-30min.

[0007] Furthermore, in step S2, the binder monomer A is one of oily hydroxy acrylic polyol and aqueous hydroxy acrylic ester dispersion; and the curing agent B is oily isocyanate.

[0008] Furthermore, in step S3, the porous polyolefin diaphragm base membrane is one of a polypropylene membrane, a polyethylene membrane, a double-layer polypropylene / polyethylene membrane, a double-layer polypropylene / polypropylene membrane, and a three-layer polyethylene / polypropylene / polyethylene membrane, wherein the maximum pore size of the porous polyolefin diaphragm base membrane is ≤90nm, the porosity is 40-90%, and the thickness is 1-20 microns.

[0009] Another object of the present invention is to provide an in-situ cured electrolyte coating diaphragm, which is prepared by the above-mentioned method for preparing an in-situ cured electrolyte coating diaphragm, and the diaphragm includes a base membrane and an electrolyte coating in-situ cured on at least one side of the base membrane.

[0010] Another object of the present invention is to provide a semi-solid-state battery, which is composed of a positive electrode plate, an in-situ cured electrolyte coating separator, and a negative electrode plate, which are sequentially stacked and then wound into a bare battery cell, and 5% electrolyte is injected into the battery, which is sealed to form a soft-pack lithium-ion battery.

[0011] Another object of the present invention is to provide a solid-state battery, which is obtained by assembling a positive electrode sheet and a negative electrode sheet into a battery and then integrating them through hot pressing, wherein the positive electrode sheet or the negative electrode sheet is obtained by coating the second dispersion on the surface of the positive electrode sheet or the negative electrode sheet respectively and performing in-situ thermal polymerization treatment. Specifically, the positive electrode sheet is composed of a positive electrode collector and a positive electrode slurry coated on the surface of the positive electrode collector, and the negative electrode sheet is composed of a negative electrode collector and a negative electrode slurry coated on the surface of the negative electrode collector (the positive electrode slurry is composed of a positive electrode active material, a conductive agent, a binder, and a solvent, and the negative electrode slurry is composed of an active material, a conductive agent, a binder, and a solvent). The in-situ solidification of the electrolyte coating improves the compatibility of the coating with the positive and negative electrode materials, reduces the solid-solid contact interface impedance, improves the ionic conductivity and flame retardant properties, and improves the safety and reliability of the lithium battery.

[0012] The present invention has the advantages that: 1. Cyclotriphosphazenes are six-membered cyclic compounds formed by alternating single and double bonds of nitrogen and phosphorus. The stable molecular structure makes them have excellent thermal stability, and their structure is easy to conduct charge, so it does not affect the performance of the battery, but also improves the cycle life of the battery. The high phosphorus content and the synergistic effect between phosphorus and nitrogen elements have extremely high flame retardant efficiency. The specific nitrogen-phosphorus compounds will decompose when heated to generate volatile gases, phosphorus-containing compounds and carbonized products. PNP bonds, POP bonds and PC bonds will form a paste. This paste will cover the surface of the residual carbon, thereby preventing combustion, achieving nitrogen-phosphorus synergistic flame retardancy, and helping to improve the electrochemical performance of the battery. When used in lithium metal batteries, it can form a Li3N-rich SEI to achieve uniform, dense, dendrite-free lithium deposition; 2. The present invention first selects a solid electrolyte material with high ionic conductivity and an efficient cyclotriphosphazene flame retardant with good electrical properties and mixes them evenly under sand milling dispersion conditions, and then undergoes in-situ thermal polymerization and curing with a two-component binder, thereby constructing an electrolyte coating diaphragm with low interface impedance in one step. Due to the stable contact between the in-situ cured electrolyte coating and the surface of the base membrane and the electrode material, good interface compatibility between the electrode and the electrolyte coating diaphragm is achieved, thereby improving the mechanical properties, interface stability and ionic conductivity of the diaphragm; 3. The flame retardant of the present invention is a small molecule monomer, which has a boiling point (110-130°C) lower than the melting point of porous polyolefin (PE 137°C, PP 170°C), and can be partially filled in the porous polyolefin base film, partially coated on the base film and coated on the surface of the solid electrolyte. After reacting with the curing agent, a part of it is filled in the pores of the polyolefin base film, and the rest reacts with the curing agent and the binder monomer to enter the resin system and become a block of the binder resin. Before the thermal runaway of the battery occurs, the flame retardant in the porous polyolefin base film absorbs heat and decomposes to form a stable covering layer to protect the base film from melting and cracking. When the temperature continues to rise, the flame retardant enters the binder resin block to play a role, absorbs heat and decomposes to form a stable covering layer, thereby improving the diaphragm's anti-puncture ability and the battery's thermal runaway temperature, and improving heat resistance and flame retardancy. When used in lithium metal batteries, a Li3N-rich SEI can be formed to achieve uniform, dense, dendrite-free lithium deposition; 4. When assembling the battery, the present invention can add ≤5% electrolyte to maintain high ion conductivity. The synergistic effect of a large number of unsaturated metal sites in the solid electrolyte structure, the structure of cyclotriphosphazene that is easy to conduct charge, and in-situ curing can quickly combine with anions in the ionic liquid and promote the dissociation of lithium salts. 5. The preparation method of the present invention is simple, low-cost, and easy to industrialize, so that the diaphragm of the present invention has broad application prospects in solid-state batteries, lithium metal batteries, and sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 It is a mechanism diagram of the interaction between the two-component adhesive and the flame retardant and the polyolefin base film after the cross-linking reaction in the present invention; Among them: the curve represents the flame retardant binder reaction cross-linked product, the black sphere represents the solid electrolyte, the ellipse represents the pore size of the base membrane, the upper layer is the coating, and the lower layer is the base membrane. DETAILED DESCRIPTION

[0014] Example 1 A method for preparing an in-situ cured electrolyte coating diaphragm comprises the following steps: (1) Preparation of the first dispersion: 100 g of solid electrolyte LATP (D50: 100 nm), 0.1 g of sodium polyacrylate, 0.5 g of hydroxycyclotriphosphazene, and 900 g of water were added to a beaker and stirred for dispersion. The mixture was then added to a sand mill and sand milled at a speed of 200 r / min for 5 min to obtain a first dispersion.

[0015] (2) adding 2 g of aqueous hydroxy acrylic acid dispersion and 0.6 g of aqueous isocyanate to the above dispersion respectively and stirring evenly to obtain a second dispersion; (3) The above dispersion was directly extruded and coated on a 20 μm polypropylene porous membrane. When heated at 40°C, in-situ thermal polymerization and curing could be rapidly performed to obtain an in-situ cured gel electrolyte coating diaphragm. The test data of various membrane properties are shown in Table 1.

[0016] A semi-solid battery, which is composed of a positive electrode sheet, an in-situ cured electrolyte coating separator, and a negative electrode sheet stacked in sequence and then wound into a bare battery cell, 5% electrolyte is injected into the battery, and sealed to form a soft-pack lithium-ion battery. The performance test data of the semi-solid battery assembled by the semi-solid battery are shown in Table 2.

[0017] Example 2 A method for preparing an in-situ cured electrolyte coating diaphragm comprises the following steps: (1) Preparation of the first dispersion: 400 g of solid electrolyte LLZO (D50: 2000 nm), 1.2 g of sodium hexametaphosphate, 4 g of aminocyclotriphosphazene, and 550 g of water were added to a beaker and stirred for dispersion. The mixture was then added to a sand mill and sand milled at a speed of 2000 r / min for 30 min to obtain a first dispersion.

[0018] (2) adding 11 g of aqueous hydroxy acrylic acid dispersion and 0.9 g of aqueous isocyanate to the above dispersion respectively and stirring evenly to obtain a second dispersion; (3) The above dispersion was directly extruded and coated on a 20 μm polypropylene porous membrane. When heated at 50°C, in-situ thermal polymerization and curing could be rapidly performed to obtain an in-situ cured gel electrolyte coating membrane. The test data of various membrane properties are shown in Table 1.

[0019] A semi-solid battery, which is composed of a positive electrode sheet, an in-situ cured electrolyte coating separator, and a negative electrode sheet stacked in sequence and then wound into a bare battery cell, 5% electrolyte is injected into the battery, and sealed to form a soft-pack lithium-ion battery. The performance test data of the semi-solid battery assembled by the semi-solid battery are shown in Table 2.

[0020] Example 3 A method for preparing an in-situ cured electrolyte coating diaphragm comprises the following steps: (1) Preparation of the first dispersion: 250 g of solid electrolyte LGPS (D50: 1000 nm), 0.8 g of polyethylene glycol, 2 g of tripropoxy-triethanolamine cyclotriphosphazene, and 750 g of water were added to a beaker and stirred for dispersion. The mixture was then added to a sand mill and sand milled at a speed of 200 r / min for 5 min to obtain a first dispersion.

[0021] (2) adding 6 g of aqueous hydroxy acrylic acid dispersion and 0.6 g of aqueous isocyanate to the above dispersion respectively and stirring evenly to obtain a second dispersion; (3) The above dispersion was directly extruded and coated on a 20 μm polypropylene porous membrane. When heated at 40°C, in-situ thermal polymerization and curing could occur rapidly to obtain an in-situ cured gel electrolyte coating diaphragm. The performance test data of the diaphragm are shown in Table 1.

[0022] A semi-solid battery, which is composed of a positive electrode sheet, an in-situ cured electrolyte coating separator, and a negative electrode sheet stacked in sequence and then wound into a bare battery cell, 5% electrolyte is injected into the battery, and sealed to form a soft-pack lithium-ion battery. The performance test data of the semi-solid battery assembled by the semi-solid battery are shown in Table 2.

[0023] Comparative Example 1: Commercial PP diaphragm Comparative Example 2: The same as Example 1, except that no cyclotriphosphazene flame retardant was added in the preparation of the first dispersion in step (1).

[0024] Comparative Example 3: The same as Example 1, except that a single-component polyurethane binder was used in the preparation of the first dispersion in step (1).

[0025] The test conditions or test standards for various performance test items of the diaphragm obtained by the present invention are as follows: 1) Ionic conductivity, breakdown voltage and tensile strength are tested according to national standards GB / T 36363-2008 "Polyolefin separator for lithium-ion batteries", GB1408.1-2006 "Electrical strength test method for insulating materials", GB / T10403-2006 "Test method for tensile properties of plastics" and ASTMD882-10 "Standard Test Method for Tensile Properties of Thin Plastic Sheeting"; 2) Flame retardant performance: The oxygen index refers to GB / T 2406.3-2022 "Determination of combustion behavior of plastics by oxygen index method Part 3: Current status of high temperature test", and the vertical combustion test is carried out according to the national standard GB T2408-2021 "Horizontal and vertical methods for determination of combustion performance of plastics".

[0026] 3) Semi-solid battery puncture test: The power battery puncture test should be carried out at an ambient temperature of 20℃±5℃. The battery connected to the thermocouple is placed in a fume hood. A steel needle with a diameter of 3-8mm is used to penetrate the battery plate at a speed of 40mm / s and a penetration force of 200KG from a direction perpendicular to the battery plate. The center of the largest surface of the battery is pierced and maintained for 1 minute. The results are shown in Table 2.

[0027] 4) Cyclic stability test: The semi-solid battery obtained above was charged and discharged at a rate of 0.5 C at room temperature, and Examples 1-3 were cycled 100, 200, and 500 times, respectively, and the battery capacity before and after the cycle was recorded, and the first charge and discharge capacity was recorded. The results are shown in Table 2.

[0028] Table 1: Results of mechanical performance test, ionic conductivity test and flame retardant performance test of in-situ cured electrolyte coating separator

[0029] Table 2: Performance test results of semi-solid battery assembled with in-situ cured electrolyte coating and separator

[0030] Example 4 A solid-state battery, wherein a second dispersion slurry is applied to the surface of a positive electrode sheet or a negative electrode sheet and subjected to in-situ thermal polymerization treatment to obtain a positive electrode sheet or a negative electrode sheet having a solid electrolyte layer, wherein the positive electrode sheet is composed of a positive electrode current collector and a positive electrode slurry applied to the surface of the positive electrode current collector, and the negative electrode sheet is composed of a negative electrode current collector and a negative electrode slurry applied to the surface of the negative electrode current collector, and the in-situ solidification of the electrolyte coating improves the compatibility of the coating with the positive and negative electrode materials, reduces the solid-solid contact interface impedance, improves the ionic conductivity and flame retardant performance, and improves the safety and reliability of the lithium battery. The above-mentioned positive and negative electrode sheets are assembled into a battery, and a solid-state battery is obtained after hot pressing and integration.

[0031] The specific preparation method comprises the following steps: 1) Preparation of the first dispersion: 350 g of solid electrolyte LATP (D50 is 300 nm), 1.0 g of polyethylene glycol, 3 g of hydroxycyclotriphosphazene, and 650 g of NMP were added to a beaker and stirred for dispersion, and then added to a sand mill and sand milled at a speed of 300 r / min for 10 min to obtain a first dispersion.

[0032] (2) adding 7 g of oil-based hydroxy acrylic resin solution and 0.7 g of oil-based isocyanate to the above dispersion respectively and stirring the mixture to obtain a second dispersion; (3) The above dispersion is directly extruded and coated on the positive electrode plate, and in-situ thermal polymerization and curing can be rapidly carried out under heating at 80°C, and finally an in-situ cured electrolyte coated positive electrode plate is obtained; the positive electrode plate and the negative electrode of the lithium battery are assembled into a battery, and a solid-state battery is obtained after hot pressing and integration. Table 2 shows the performance test data of the solid-state battery of the present invention.

[0033] Interface impedance test: The prepared composite electrode and lithium metal sheet were assembled into a button cell, and the AC impedance was tested in an electrochemical workstation using the AC impedance method, with the voltage amplitude set to 5 mV and the frequency range of 0.1 Hz to 1 MHz. The results are shown in Table 2.

[0034] Cyclic stability test: The solid-state battery obtained by hot pressing integration was charged and discharged at a rate of 0.5 C at room temperature. Example 4 was cycled 100, 200, and 500 times, and the battery capacity before and after the cycle was recorded, and the first charge and discharge capacity was recorded. The results are shown in Table 3.

[0035] Table 3: Performance test results of the assembled solid-state battery with positive and negative electrodes coated with in-situ cured electrolyte coating

Claims

1. A method for preparing an in-situ cured electrolyte coating diaphragm, characterized in that: The following steps are involved: S1. Prepare a first dispersion: stir a solid electrolyte material, a dispersant, and a flame retardant monomer in a solvent, and then place the mixture in a sand mill to completely disperse the mixture to obtain a first dispersion, wherein the mass ratio of the solid electrolyte material, the dispersant, the flame retardant monomer, and the solvent is (10-40): (0.01-1.2): (0.05-4): (55-90), and the flame retardant monomer is a cyclotriphosphazene flame retardant containing a hydroxyl group or an amino group; S2. Preparing a second dispersion: adding a two-component binder to the first dispersion, wherein the two-component binder is composed of a binder monomer A and a curing agent B, wherein the mass ratio of the binder monomer A, the curing agent B and the solid electrolyte material in the first dispersion is (2-10): (0.06-1): (89-98); S3. Prepare the diaphragm: directly extrusion-coat or dip-coat the second dispersion on the porous polyolefin base membrane, and perform in-situ thermal polymerization and curing at 40-80° C. to obtain an in-situ cured electrolyte coating diaphragm.

2. The method for preparing an in-situ cured electrolyte coating diaphragm according to claim 1, characterized in that: In the step S1, the solid electrolyte material is at least one of LATP, LAGP, LLZTO, LLZO, sulfide-oxide electrolyte or LGPS, and the D50 of the solid electrolyte material is from 100nm to 2000nm; the dispersant is at least one of sodium hexametaphosphate, sodium polyphosphate, sodium dodecyl sulfate, polyacrylamide, sodium polyacrylate, polybutyl acrylate-styrene-acrylic acid, polyethylene glycol, polyvinyl pyrrolidone, and maleic anhydride-styrene copolymer; the flame retardant monomer is at least one of hydroxycyclotriphosphazene, aminocyclotriphosphazene, and tripropoxy-triethanolamine cyclotriphosphazene; the sand mill speed is 200-2000 r / min, and the sand milling time is 5-30min.

3. The method for preparing an in-situ cured electrolyte coating diaphragm according to claim 1, characterized in that: In the step S2, the binder monomer A is one of oily hydroxy acrylic polyol and aqueous hydroxy acrylic ester dispersion; the curing agent B is oily isocyanate.

4. The method for preparing an in-situ cured electrolyte coating diaphragm according to claim 3, characterized in that: In step S3, the porous polyolefin diaphragm base film is one of a polypropylene film, a polyethylene film, a double-layer polypropylene / polyethylene film, a double-layer polypropylene / polypropylene film, and a three-layer polyethylene / polypropylene / polyethylene film, wherein the porous polyolefin diaphragm base film has a maximum pore size of ≤90nm, a porosity of 40-90%, and a thickness of 1-20 microns.

5. An in-situ cured electrolyte coating diaphragm, characterized in that: The diaphragm is prepared by the method for preparing an in-situ cured electrolyte coating diaphragm according to any one of claims 1 to 4, and the diaphragm comprises a base film and an electrolyte coating in-situ cured on at least one surface of the base film.

6. A semi-solid battery, characterized in that: The semi-solid battery is composed of a positive electrode sheet, an in-situ cured electrolyte coating diaphragm, and a negative electrode sheet stacked in sequence and then wound into a bare battery cell. 5% electrolyte is injected into the battery and sealed. Into a soft pack lithium ion battery.

7. A solid-state battery, characterized in that: The solid-state battery is obtained by assembling a positive electrode sheet and a negative electrode sheet into a battery and then integrating them through hot pressing, wherein the positive electrode sheet or the negative electrode sheet is obtained by coating the second dispersion in claim 1 onto the surface of the positive electrode sheet or the negative electrode sheet respectively and performing in-situ thermal polymerization treatment.

Citation Information

Patent Citations

  • High-safety lithium ion battery and preparation method thereof

    CN114171779A

  • Gel electrolyte for sodium ion battery as well as preparation method and application of gel electrolyte

    CN116722214A

  • Lithium ion battery and preparation method thereof

    CN118117162A

  • Electrochemical display element

    JP2007163865A

  • A method of manufacturing separator for electrochemical device and separator for electrochemical device manufactured thereby

    KR1020160129567A

Cited By

  • Battery monomer as well as preparation method and application thereof

    CN122338177A